Yagé: Western crisis and spiritual work - Ávila, Javier; Pedroza, Mariana; Angulo, Oscar (Universidad y Salud, 2019)
Introduction: In the face of epistemological and systemic crisis in Western civilization, yagé emerges as an alternative that invites a deep axiological reponderation. The yagé ritual demonstrates the limits of modern medical knowledge, giving guidance to a transdisciplinary approach. On the other hand, there are consequences of insertion into the free market, involving profit problems at the expense of original traditions. Thus, the concept of "spiritual work" is explored as a practice that seeks to dislodge itself from commercial colonialism while moving away from the modern medical model. Objective: To reflect on the incorporation of the yage ritual in the West and its possibilities as an epistemological and medical alternative. Materials and methods: Review of articles from the specialized Web of Science database, with the keyword: “ayahuasca”. Results: The information was structured considering aspects related to: (a) the context of incorporation of yagé into the West, (b) the limits of modern medical knowledge and (c) the problems of insertion into the free market. Conclusions: The diagnosis of the epistemological rupture with the West is supported while recognizing the initial state of the investigations and the lack of documented evidence in order to enter into a more fruitful debate.